Analysis of Character Education for Social and Emotional Development in Early Childhood - Retnaningrum, Wulandari; Hazhari, Alvan (Raudhatul Athfal: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
This study aims to analyse the role of character education in improving social-emotional development in early childhood. The problem in this study is that character education in early childhood education settings still faces various challenges such as a lack of training for educators, limited resources and a lack of parental involvement. This research method is conducted through a literature review and empirical analysis of various character education programmes in early childhood education institutions. The participants in this study were researchers, educators, parents and early childhood practitioners. The results show that character education can have a significant impact on children's ability to manage emotions, build social relationships and adapt to the environment. The follow-up to this research is to design a character education programme that is structured and adapted to the stage of early childhood development, and that integrates values such as empathy, cooperation, independence and tolerance into children's daily activities.